1992
DOI: 10.1111/j.1365-3040.1992.tb01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of salt tolerance and osmotic adjustment of low‐sodium and high‐sodium subspecies of the C4 halophyte, Atriplex canescens

Abstract: The relationship between Na''^ accumulation and salt tolerance was tested by comparing subspecies of the halophyte, Atriptex canescens (fourwing saltbush), that differed markedly in Na^ content and Na:K ratios. Above ground tissues of one low-sodium and two high-sodium subspecies were compared with respect to cation accumulation, osmotic adjustment and growth along a salinity gradient in greenhouse trials. Plants of each subspecies were grown for 80 d on 2-2, 180, 540 and 720mol m~^ NaCL At harvest, A. canesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 24 publications
(42 reference statements)
3
26
0
Order By: Relevance
“…Contrary to one previous distinction made about glycophytes and halophytes, it is now known that both types of species can limit Na + uptake into the shoot, i.e. salt tolerance in halophytes is not necessarily dependent on high levels of Na + accumulation in the shoot (Glenn et al, 1992). The high degree of NaCI induction of plasma membrane H + -ATPase mRNA accumulation in A. nummularia roots as determined by analyses of the entire organ was apparently the result of increased transcript levels in cells of the elongation and differentiation zones.…”
Section: Discussionmentioning
confidence: 59%
“…Contrary to one previous distinction made about glycophytes and halophytes, it is now known that both types of species can limit Na + uptake into the shoot, i.e. salt tolerance in halophytes is not necessarily dependent on high levels of Na + accumulation in the shoot (Glenn et al, 1992). The high degree of NaCI induction of plasma membrane H + -ATPase mRNA accumulation in A. nummularia roots as determined by analyses of the entire organ was apparently the result of increased transcript levels in cells of the elongation and differentiation zones.…”
Section: Discussionmentioning
confidence: 59%
“…Osmotic adjustment to saline substrates is achieved by accumulation of alkali salts (Flowers & Yeo, 1988). Therefbre, the calculated cation concentration, doubled because of the accompanying anions, may be considered an estimate of osmotic pressure (Glenn et al, 1992). Following this estimate, the results suggest a similar osmotic adjustment in both subspecies.…”
Section: I S C U S Si O Nmentioning
confidence: 72%
“…In such plants, K + accumulation accounts for barely 4% of total cation contribution to osmotic adjustment, and their Na + /K + ratios may be as high as 30 in seawater-level salinity (Naidoo and Rughunanan 1991). On the other hand, Glenn et al (1992) demonstrated that halophytes that appeared to discriminate against Na + , in favour of K + , were as tolerant of salt as those that appeared to favour Na + for osmotic adjustment. In the case of non-halophytes, it is clear that some species discriminate against Na + more than others by lowering [Na + ] in the leaves, particularly in the cytoplasm, balanced by higher cytoplasmic K + concentrations, often increasing salt tolerance (Hajibagheri et al 1989).…”
Section: Na+/k+ Discriminationmentioning
confidence: 99%